Conceptual disorganization as a mediating variable between visual learning and metacognition in schizophrenia - Montemagni, Cristiana; Brasso, Claudio; Bellino, Silvio; Bozzatello, Paola; Villari, Vincenzo; Rocca, Paola (Frontiers in Psychiatry, 2023)
Objectives: to evaluate the relative contributions of visual learning and conceptual disorganization to specific metacognitive domains in a sample of outpatients with stable schizophrenia.Methods: Ninety-two consecutive outpatients with stable schizophrenia were recruited in a cross-sectional study. We analyzed the data with 5 path analyses based on multiple regression to analyse the specific effect of visual learning on metacognitive capacity and metacognitive domains and the possible mediating role of conceptual disorganization.We found that (i) visual learning was negatively correlated to metacognitive capacity and its domains on the one hand and conceptual disorganization on the other hand; (ii) conceptual disorganization was negatively associated with metacognition and its domains; (iii) when the mediation effect was considered, conceptual disorganization fully mediated the relationship between visual learning and mastery, whereas it served as a partial mediator of the effect of visual learning on the other metacognition domains, i.e., selfreflectivity, understanding other minds, and decentration.Conclusions: These results delineate an articulated panorama of relations between different dimensions of metacognition, visual learning and conceptual disorganization. Therefore, studies unable to distinguish between different components components of metacognition fail to bring out the possibly varying links between neurocognition, disorganization, and metacognition.